PERKAWINAN GADIS HAMIL DALAM PANDANGAN HUKUM ISLAM DAN HUKUM POSITIF INDONESIA - Hutajulu, Andreas Fransiskus; Hutajulu, Maria Margareta (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Marriage of pregnant girls according to Islamic Law has various views from various schools of thought. The Shafi'i and Hanafi schools of thought permit the marriage of pregnant women due to adultery, although with several provisions, such as not being allowed to have sexual intercourse before the woman gives birth. In the view of the Maliki and Hanbali schools of thought, the marriage is still valid, but the perpetrator of adultery is not recommended to marry a pregnant woman before giving birth, in order to maintain the clarity of lineage. All schools of thought agree that women who are pregnant due to adultery are not required to undergo the iddah period, because the iddah aims to ensure the legitimate lineage of the child. Meanwhile, according to Law Number 1 of 1974 concerning Marriage, although it does not explicitly regulate the marriage of pregnant girls, this law provides leniency through a marriage dispensation mechanism in religious or state courts, which allows couples to marry even if one party is pregnant before marriage. Children born from this marriage remain legally valid, and this marriage is recognized as long as it meets the applicable terms and conditions, including court approval. Thus, both in Islamic law and positive Indonesian law, the marriage of a pregnant girl can be considered valid as long as it meets the applicable legal provisions.Keywords: Marriage, Girl, Pregnant.